Factitiously Elevated Total Triiodothyronine in a Euthyroid Patient with Multiple Myeloma - Kaushik Mandal; Damilola Ashorobi; Alice Lee; Huijuan Liao; Salini C. Kumar; David S. Rosenthal (Case Reports in Endocrinology)
Sporadic reports of factitious elevations of thyroid hormones related to laboratory interference from autoantibodies and multiple myeloma paraproteins have appeared in the literature. Such clinically confusing laboratory results can lead to erroneous diagnoses and inappropriate treatments. We report an additional case of a patient with multiple myeloma and an IgG paraproteinemia who had such a spurious elevation of total T3 complicating her levothyroxine management of hypothyroidism. In addition, we alert clinicians that differences in performance characteristics between various manufacturers’ test platforms may also cause spurious reports.